2021
DOI: 10.1183/23120541.00837-2020
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mortality during long-term follow-up in pulmonary arterial hypertension

Abstract: The European Society of Cardiology (ESC) and European Respiratory Society (ERS) guideline recommendation of comprehensive risk assessments, which classify patients with pulmonary arterial hypertension (PAH) as having low, intermediate or high mortality risk, has not been evaluated during long-term follow-up in a “real-life” clinical setting. We therefore aimed to investigate the utility of risk assessment in a clinical setting for up to 5 years post diagnosis.Three hundred and eighty-six patients with PAH from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…The main limitation of the 2015 ESC/ERS three-strata, risk-assessment tool is that 60-70% of the patients are classified as intermediate risk [274,[293][294][295][297][298][299][300][301][302][303]. An initial attempt to substratify the intermediate-risk group has been proposed, using a modified mean score in the SPAHR equation (with low-intermediate, 1.5-1.99 and high-intermediate, 2.0-2.49 as cut-offs), where the high-intermediate group was associated with worse survival [302]. There have also been attempts to further improve risk stratification by exploring the additional value of new biomarkers [304], or by measuring RV structure and function by echocardiography and cMRI [231,305,306].…”
Section: Comprehensive Prognostic Evaluation Risk Assessment and Trea...mentioning
confidence: 99%
See 2 more Smart Citations
“…The main limitation of the 2015 ESC/ERS three-strata, risk-assessment tool is that 60-70% of the patients are classified as intermediate risk [274,[293][294][295][297][298][299][300][301][302][303]. An initial attempt to substratify the intermediate-risk group has been proposed, using a modified mean score in the SPAHR equation (with low-intermediate, 1.5-1.99 and high-intermediate, 2.0-2.49 as cut-offs), where the high-intermediate group was associated with worse survival [302]. There have also been attempts to further improve risk stratification by exploring the additional value of new biomarkers [304], or by measuring RV structure and function by echocardiography and cMRI [231,305,306].…”
Section: Comprehensive Prognostic Evaluation Risk Assessment and Trea...mentioning
confidence: 99%
“…c Observe that 6MWD is dependent upon age, height, and burden of comorbidities. d To harmonize with the four-strata model shown in Table18, the BNP and NT-proBNP cut-off levels have been updated from the 2015 version based on data from the REVEAL registry, acknowledging that the European validation studies have used the original cut-off levels[274,292,293,295,296,302]. e cMRI parameters adapted from Section 6.2.2.2. https://doi.org/10.1183/13993003.00879-2022…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have shown that the use of additional variables derived from echocardiography, right heart catheterization or blood gas analysis improved risk prediction [11][12][13][14]. As an alternative model, the SPAHR group recently proposed a modification of their original approach defining a calculated score of 1.5-1.99 as intermediate-low risk and a score of 2.0-2.4 as intermediate-high risk [15]. This approach showed promising results with further discrimination within the intermediate-risk group, albeit based on a relatively small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…These changes can significantly affect psychological and physical conditions of patients in different ways. For example, PAH patients may have feelings of uncertainty about their future, significant economic burden (7), a high risk of maternal mortality (30-55%) (7,8), and heavy side effects of medical therapies (9). All of these could have a negative effect on a patient's mental status, resulting in the occurrence of depression and anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%